Podocan and Adverse Clinical Outcome in Patients Admitted With Suspected Acute Coronary Syndromes - Andersen, Thomas; Ueland, Thor; Aukrust, Pål; Nilsen, Dennis W.; Grundt, Heidi; Staines, Harry; Kontny, Frederic (Frontiers in Cardiovascular Medicine, 2022)
1 Abstract 1.1 Background: Markers of bone and extracellular matrix (ECM) remodeling may be associated with adverse outcomes in atherosclerotic cardiovascular disease. Podocan is a newly discovered ECM glycoprotein, previously not studied in a chest pain population. We wanted to study the association between Podocan levels on admission and risk of adverse outcome in a chest pain population with suspected acute coronary syndromes. 1.2 Methods: A total of 815 patients from the Risk markers in Acute Coronary Syndrome (RACS) trial with suspected coronary chest pain were followed for 7 years. Blood samples were taken immediately after inclusion and stored in biobank. Associations between Podocan and endpoints were assessed with cox proportional hazards analyses. 1.3 Results: The median admission level of Podocan was 0.674 ng/mL (0.566-0.908 ng/mL). No significant association was found between Podocan quartile levels and all-cause death, neither at 1 year, nor at 2- or 7-years follow-up (p>0.05 for all). Furthermore, no significant association could be shown for Podocan and cardiac death, myocardial infarction (MI), stroke, or the composites of all-cause death/MI/stroke or cardiac death/MI/stroke (p>0.05 for all). Similarly, in a subgroup of Troponin T positive patients (n=432) there was no significant association between Podocan and any of the outcome measures (p>0.05 for all endpoints and points in time). 1.4 Conclusions: Podocan, a novel ECM biomarker, is not associated with all-cause mortality or other major cardiovascular adverse events in patients admitted with acute chest pain suspected to be of coronary origin. ClinicalTrials.gov Identifier: NCT00521976